Prepletene polimerne mreže za dodelavo usnja z brizganjem in zamreženjem "in situ" - Anžlovar, Alojz (Materiali in tehnologije, 2000)
The possibility of using mixtures of polyurethane (PU) and polymethacrylate (PM) prepolymers for leather finishing by spraying and by forming IPNs on the leather surface was investigated. By testing the finished leather according to the standards the applicability of these IPN finishes was estimated.
Keywords: usnje; polimerne mreže; poliuretani; brizganje